Penggunaan skala prestasi kanak-kanak Mccharty (MSCA) sebagai alat pengukur tahap cerdik pandai kanak-kanak di Malaysia - Shamsul Bahari Shamsudin; Zailina H.; Jamal Hisham H.; Rohani A. (1997)
The objectives of this study are to test the applicability and reliability of the McCarthy Scales of Children’s Abilities (MSCA) as a measurement of intelligent quotient (IQ) among Malaysian children of Malay descent. A total of 212 children from 4 primary schools located in Kuala Lumpur and Trengganu were selected for this study through stratified random sampling according to age and sex. The selected students were subjected to the McCarthy Scales of Children’s Abilities (MSCA) IQ test battery. The test battery is divided into 6 scales such asVerbal, Perceptual-Performance, Quantitative, Memory, Motor and General Cognitive. The Verbal, Perceptual-Performance and, Quantitative do not overlap in content and when they are added together, they form the General Cognitive Index which reflects on the children’s general intelligence. The MSCA was translated from English to Malay language and some of the examples in the test were adapted to the local situations. The results on 18 tests which made up the 5 scales showed good reliability since the alpha values were greater than 70% for all the children tested or when they are grouped into schools or study areas.